Changes in the Intestine Microbial, Digestive, and Immune-Related Genes of Litopenaeus vannamei in Response to Dietary Probiotic Clostridium butyricum Supplementation - Duan, Yafei; Wang, Yun; Dong, Hongbiao; Ding, Xian; Liu, Qingsong; Li, Hua; Zhang, Jiasong; Xiong, Dalin (Frontiers in Microbiology, 2018)
The intestine barrier serves as the front-line defence in shrimp. Clostridium butyricum (CB) can produce butyric acid that provides energy for the intestine epithelial cells of the host. However, the effects of dietary CB on the intestine microbiome and the digestion and immunity of the host is not clear. In this study, we therefore investigated the composition and metabolic activity of the intestine microbiome, and digestive and immune-related gene expression in Litopenaeus vannamei fed with diets containing different levels of CB: basal diet (control), 2.5 109 CFU kg-1 diet (CB1), 5.0 109 CFU kg-1 diet (CB2), and 1.0 1010 CFU kg-1 diet (CB3) for 56 days. Dietary CB altered the composition of the intestine microbiome. Specifically, the dominant bacterial phylum Proteobacteria was enriched in the CB3 group and weakened in the CB1 and CB2 groups. The Bacteroidetes was enriched in the CB1 and CB2 groups and weakened in the CB3 group. The Firmicutes was enriched in all three CB groups. At the genus level, the potential pathogen (Desulfovibrio and Desulfobulbus) were weakened, and beneficial bacteria (Bacillus, Clostridium, Lachmoclostridium, Lachnospiraceae, and Lactobacillus) were enriched in response to dietary CB; these might contribute to the expression of the host digestive genes (α-amylase, lipase, trypsin, fatty acid-binding protein, and fatty acid synthase) and immune-related genes (prophenoloxidase, lipopolysaccharide and β-1,3-glucan binding protein, lysozyme, crustin, and superoxide dismutase). Additionally, CB enhanced the bacterial metabolism, especially that of carbohydrates, polymers, amino acids, carboxylic acids, and amines. These results revealed that dietary CB had a beneficial effect on the intestine health of L. vannamei by modulating the composition of the intestine microbiome, enhancing the microbial metabolism activity, and promoting the digestion and immunity of the host. The optimal dietary supplementation dosage was found to be 5.0 109 CFU kg-1 in the diet.